El sistema colombiano escuela nueva: un instrumento eficaz para compensar desventajas socioeconómicas de sus alumnos (2021)
Previous research has suggested that the Escuela Nueva methodology has an effect that could offset the incidence of socioeconomic factors on the academic performance of elementary school students. This work verifies whether said results are currently replicated for students in the ninth year of high school in the Postprimaria model with the methodology of Escuela Nueva in the department of Caldas. For this, two multilevel models are calculated to analyze the scores in the areas of language and mathematics achieved in the standardized national test SABER 9 of 2017. The results show that on average the students within the Escuela Nueva system present a lower performance in the two areas studied if compared with students at Traditional School. However, unlike what happens with the traditional school students, the scores of the Escuela Nueva students are not significantly related to the educational level of their parents. This suggests that it may exist a compensatory effect on socioeconomic factors, such as the level of education of the parents, related to Escuela Nueva model in Postprimaria in Department of Caldas.